Safer by Design and Trump Rights of Citizens. - Kallhoff, Angela (NanoEthics, 2017)
The debate on 'safer by design' has primarily been focused on strategies to render products safer during the design process. This article focuses on correlated basic legal rights of citizens. The reference to 'trump rights' is helpful in highlighting two normative claims: Firstly, products that are 'safer by design' are suitable instruments to protect the bodily integrity and health of potential users. Both figure as trump rights in Ronald Dworkin's sense. In this perspective, 'safer by design' strategies can guarantee some most basic rights of citizens. Secondly, the debate on trump rights also suggests that safety needs to be regarded as part of a more comprehensive normative framework. Even trump rights are competitive in that a plurality of rights needs to be respected. A final section gives evidence that both claims resonate with recent insights in debate on the precautionary principle. This section also highlights the recent emphasis on environmental concerns.